2013
DOI: 10.1210/er.2012-1044
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic Diabetes Insipidus: Essential Insights into the Molecular Background and Potential Therapies for Treatment

Abstract: The water channel aquaporin-2 (AQP2), expressed in the kidney collecting ducts, plays a pivotal role in maintaining body water balance. The channel is regulated by the peptide hormone arginine vasopressin (AVP), which exerts its effects through the type 2 vasopressin receptor (AVPR2). Disrupted function or regulation of AQP2 or the AVPR2 results in nephrogenic diabetes insipidus (NDI), a common clinical condition of renal origin characterized by polydipsia and polyuria. Over several years, major research effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
186
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(190 citation statements)
references
References 181 publications
3
186
0
1
Order By: Relevance
“…The most common adverse effect of Li + therapy, affecting approximately 50% of patients, is Li + -induced nephrogenic diabetes insipidus (Li-NDI), characterized by polydipsia, polyuria, and a limited renal response to the antidiuretic hormone, arginine vasopressin (AVP) (2). The polyuric effects of Li + are associated with a marked decrease in the abundance of the water channel aquaporin-2 (AQP2) in collecting duct (CD) principal cells (PCs), accompanied by a large increase in the ratio of intercalated cells (ICs) to PCs along the CD system (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The most common adverse effect of Li + therapy, affecting approximately 50% of patients, is Li + -induced nephrogenic diabetes insipidus (Li-NDI), characterized by polydipsia, polyuria, and a limited renal response to the antidiuretic hormone, arginine vasopressin (AVP) (2). The polyuric effects of Li + are associated with a marked decrease in the abundance of the water channel aquaporin-2 (AQP2) in collecting duct (CD) principal cells (PCs), accompanied by a large increase in the ratio of intercalated cells (ICs) to PCs along the CD system (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Binding of AVP to the V2R leads to cAMP-mediated translocation of aquaporin-2 to the apical plasma membrane. This regulation of aquaporin-2 water channel localization is crucial for increasing urine osmolality and reducing urine output in humans (3). For precise regulation, the signal transduction of the activated GPCR has to be terminated to limit the effect in the target cells (4).…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of the majority of mutations in FNDI located in the NPII moiety followed by the signalling peptide of the AVP precursor has been consistent in a large number of unrelated FNDI kindred studies since then. 20 Nevertheless, studies have found a few cases of autosomal dominant mutations associated with FNDI affecting specifically positions 2 and 3 of AVP ( Figure 1B). Rittig et al 8 found the same missense mutation identified in the present study in Turkish kindred with FNDI.…”
Section: Discussionmentioning
confidence: 99%